Component Representation for Shock Qualified Foundation Structure. (2003) - Coats, Timothy; Cooper, Michael; Arden, Kevin; Russell, Fred
Abstract : Navy ship foundations are typically designed for shock using the Navy's Dynamic Design Analysis Method. The NAVSEA 0908-LP-000-3010, Rev. 1 manual states that a component modeled as a lumped mass with rigid links should not provide constraint to the support structure. This ensures foundations are designed to withstand all shock loads without accounting for additional stiffness provided by the component. Investigations are provided herein to illustrate the trade-offs and consequences of several approaches for component representations. The observations reinforce the notion that one must give careful consideration for the system being modeled, the expected modal characteristics, and compliance with NAVSEA 0908-LP-000-3010, Rev. 1.